Social Criticsm in The Short Story “Lailatu Zifaf (Wedding Night)” By Najib Kailani - Muhammad Thoriqussuud; Malik Fahad (Journal of Arabic Literature (JaLi), 2022)
Abstract: Every literary work created conveys certain messages about social life from the author's point of view, these messages may be the author's way of addressing real social problems. Social criticism contributed to clarifying this issue. Social criticism will show readers that every literary work is a mirror of social and cultural life.The purpose of this research is to describe the forms of social criticism in the short story "Lailatu Zifaf (wedding night) by Najib Kailani from the perspective of literary sociology. This research uses a sociology of literature approach that focuses on the theory of social criticism. The data collection technique used in this research is note-taking technique. The data that has been collected was analyzed using a descriptive method with content analysis. The data source of this research is the short story “Lailatu Zifaf (wedding night) by Najib Kailani. The results showed the forms of social criticism in the short story "Lailatu Zifaf (wedding night) by Najib Kailani, namely (1) social criticism of forced marriages, (2) social criticism of the barbarity of husbands against their wives, (3) social criticism of the perceived position of women lower than men. And there are two forms of delivery of social criticism in this short story, namely (1) direct delivery, and (2) indirect delivery.